An engineering project for semiconductor industry wastewater treatment - TU Lingbo (Gongye shui chuli, 2024)
The semiconductor industry wastewater is complex due to it contains large amount of pollutants such as heavy metals, toxic cyanide, fluoride, nitrogen, and phosphorus, etc. Meanwhile, the poor biodegradability and low C/N makes it difficult to directly use biological methods for treatment. The sewage treatment plant in a certain high-tech industrial park adopts the treatment process of “grille+aeration sedimentation tank+high-efficiency sedimentation tank+advanced A2/O+MBR+disinfection tank”. The changes of influent and effluent water quality during the actual operation for 5 months were explored. The results showed that the treatment process had a good removal effect on pollutants. During operation, pollutants such as suspended solids, COD, NH4+-N, TN, TP, and fluoride in effluent were maintained below 4, 26, 1, 8, 0.1, and 1.5 mg/L, respectively, which always met the first level class A standards of Discharge Standard of Pollutants for Municipal Wastewater Treatment Plant (GB 18918-2002). In addition, the electricity cost of water treatment was about 0.536 yuan/m3, the chemicals cost was about 0.220 yuan/m3, and the direct operating cost was about 0.756 yuan/m3.